Nutritional status of children with clinical conditions. Issue 3 (June 2017) - Murphy, Alexia J.; Hill, Rebecca J.; Buntain, Helen; White, Melinda; Brookes, Denise; Davies, Peter S.W.
Summary: Background & aims: Nutritional status is an important consideration in many pediatric clinical conditions. This paper aimed to examine and compare the nutritional status, represented by body cell mass (BCM), of children with cancer, Crohn's disease (CD), cystic fibrosis (CF) and anorexia nervosa (AN). Methods: Anthropometry was measured and BCM was calculated from whole body potassium-40 counting in 259 children being treated for clinical conditions (n = 66 cancer; n = 59 AN; n = 75 CF; n = 59 CD) and 108 healthy children. BCM was adjusted for height (BCMI) and expressed as a Z-score relative to laboratory reference data. Results: The CD (−0.80 ± 1.61; p = 0.0001) and AN (−1.13 ± 0.99; p = 0.0001) groups had significantly lower BMI Z-score than the healthy control (0.13 ± 0.75), cancer (0.50 ± 1.40) and CF groups (−0.09 ± 0.95). The cancer (−1.16 ± 1.60; p = 0.0001), CD (−1.13 ± 1.36; p = 0.0001) and AN (−0.97 ± 1.18; p = 0.0001) groups had significantly reduced BCM compared to the healthy control (0.07 ± 0.93) and CF group (0.31 ± 1.08). According to BCMI Z-score, 42.4% of patients with cancer, 41.7% of the patients with CD, 27.1% of patients with AN, and 4.0% of patients with CF were considered malnourished. Conclusions: This study demonstrates that children undergoing treatment for clinical conditions may have alterations in BCM, independent of BMI. Children with cancer, CD and AN all had a high prevalence of malnutrition. Assessment of body composition, not just body size, is vital to understand nutritional status in children with clinical conditions.